Liberal Feminism in the Little Women Novel by Louisa May Alcott (1868) - Selvi Eka Putri; Yenni Rosana (Literary Criticism, 2018)
The Little Women by Louisa May Alcott is a fictional novel, the setting during the civil war period in America in the 19th century. This novel tells the story of the March family who face so many challenges in their life. This study aims to analyze the March family members’ characters and find out how the women in March family were struggling to solve the difficulties in their life using the liberal feminism theory, which prioritizes women's freedom in achieving their rights. Following the theory, the women characters in this novel were classified into two themes. The first theme is leadership which including being a leader and being an influential figure. The second theme is independence, which is also divided into being independent thinkers and independent to support themselves and family. Keywords: Women, Struggle, Little Women Novel, Liberal Feminism theory